The Influence of Social Media Marketing on Brand Loyalty with the Mediation of Brand Love and Brand Trust among Minimarket Consumers - Susanti, Dewi; Panjaitan, Arop Ria Saulina (Yayasan Gema Bina Nusantara, 2024)
In the digital era, Social Media Marketing (SMM) has become a primary tool for businesses to convey information and build relationships with consumers. This study aims to explore the relationships among Social Media Marketing, Brand Love, Brand Trust, and Brand Loyalty within the retail industry context, focusing specifically on the minimarket sector. The sample consisted of 147 respondents who were customers of minimarkets in West Jakarta, followed the minimarkets’ Instagram accounts, and had made at least five purchases within the past three months. Data were analyzed using Path Analysis with PLS-SEM, including tests for validity, reliability, and hypothesis testing. Based on the literature review and proposed hypotheses, this study examined the direct and mediating effects of Brand Love and Brand Trust on the relationship between Social Media Marketing and Brand Loyalty. The findings indicate that Social Media Marketing has a positive effect on both Brand Love and Brand Trust, which in turn enhance Brand Loyalty. Furthermore, both Brand Love and Brand Trust were found to mediate the relationship between Social Media Marketing and Brand Loyalty. This research provides valuable insights for retail companies in leveraging social media to improve customer loyalty and strengthen brand-consumer relationships.